Gemcitabine Plus Cisplatin Versus Non-Gemcitabine and Cisplatin Regimens as Neoadjuvant Treatment for Cholangiocarcinoma Patients Prior to Liver Transplantation: An Institution Experience - Abdelrahim, Maen; Esmail, Abdullah; Xu, Jiaqiong; Umoru, Godsfavour; Al-Rawi, Hadeel; Saharia, Ashish; Abudayyeh, Ala; Victor, David; McMillan, Robert; Kodali, Sudha; Ghobrial, Rafik M. (Frontiers in Oncology, 2022)
Background Cholangiocarcinoma management is constantly being updated in view of existing evidence in order to establish practice guidelines and consensus statements. However, the available treatment guidelines to optimize outcomes for cholangiocarcinoma patients who require liver transplantation are still controversial. This study contributing to the cholangiocarcinoma care field by investigating a new promising neoadjuvant therapy that might be help to grant the liver transplant option to the patients with cholangiocarcinoma. Here, we evaluate and compare the potential efficacy of chemotherapy combination of Gemcitabine plus Cisplatin versus non- Gemcitabine and Cisplatin regimens as a neo-adjuvant treatment for cholangiocarcinoma patients prior to liver transplantation. Methods In this retrospective study, patients with locally advanced, unresectable, hilar, or intrahepatic cholangiocarcinoma with no evidence of extrahepatic disease or vascular involvement were treated with either the combination of neo-adjuvant Gemcitabine plus Cisplatin with no radiation or other standard options of neo-adjuvant treatment. All patients included received chemotherapy prior to being listed for liver transplantation at a single cancer center in collaboration with the same institution’s transplant center according to an open-labeled, and centers-approved clinical management protocol. Patients were listed for liver transplantation if they had a minimum of six months of scans showing response or confirmation of disease stability. The primary endpoints were the overall survival and recurrence-free survival after liver transplantation. This report, which was censored on March 18, 2022. Results Out of a total of 707 liver transplant recipients were screened, 37 patients were confirmed with a diagnosis of cholangiocarcinoma and only 18 patients (11 males and 7 females) with a median age of 61.83 [interquartile range: 58.27-68.74] met inclusion criteria. Of the 18 patients enrolled, 10 received Gemcitabine/Cisplatin, while 8 patients received either Gemcitabine monotherapy or Capecitabine or FOLFIRI. Months for recurrence after transplantation was 20.1 (IRQ: 20.1-20.1) in the Gemcitabine/Cisplatin group and 9.5 (8.9-12.47) months in the non-Gemcitabine/Cisplatin group (p-value=0.18). Median months of follow-up in the Gemcitabine/Cisplatin group was 28.35 (27.1-32.23) months versus 40.12 (20.6-56.22) months in the non-Gemcitabine/Cisplatin group (p-value=0.33). In non-Gemcitabine/Cisplatin patients, overall survival was 75% (95% CI 31-93%) at both years 1 and 2; 63% (95% CI 23-86%) at years 3 to 5. In Gemcitabine/Cisplatin patients, overall survival was 100% (95% CI 100-100%) at both years 1 and 2; 75% (95% CI 13-96%) at years 3 to 5. Three non-Gemcitabine/Cisplatin patients died at 328 days, 340 days, and 896 days, respectively. One Gemcitabine/Cisplatin patient died at 885 days. Conclusion Our findings suggest improved overall survival outcomes with Gemcitabine plus Cisplatin as neo-adjuvant treatment with no concomitant radiation compared to non-Gemcitabine/Cisplatin regimens in patients with cholangiocarcinoma prior to liver transplantation.